Novel luminescent materials based on silica doped with an europium(III) complex of 2,6-dihydroxybenzoic acid: the crystal structure of [(nBu4N)2[Eu(2,6-Hdhb)(5)(H2O)(2)] - Soares-Santos, P. C. R. (2004)
Novel luminescent materials were prepared by introducing a new Eu3+ complex of 2,6-dihydroxybenzoic acid (2,6-H2dhb) into a silica gel made by the sol–gel method. The crystal structure of the resulting complex [nBu4N]2[Eu(2,6-Hdhb)5(H2O)2] was determined using single-crystal X-ray diffraction. The compound was further characterised using FTIR, FT-Raman and elemental analysis. Photoluminescence measurements were performed for the isolated Eu(III) 2,6-dihydroxybenzoate complex and also for the related silica composite material.